STUDI KOMPARATIF PERAN KOPERASI SIMPAN PINJAM BINA BERSAMA DAN BMT INSANI DALAM PENGEMBANGAN UMK DI KOTA PADANGSIDIMPUAN - Indah Komala Sari Siregar (Ekonomi dan Keuangan, 2013)
This Reasearch is aimed to see what the similarities and difference between Bina Bersama Saving-loan Cooperation and BMT Insani Cooperation. The concern Variable of this reasearh are Capital, Income, developing business partner, enterprise protection, and people’s satisfication level to cooperation service. The data that used in this reasearch is directly recieve from between Saving-loan Cooperation Bina Bersama and BMT Insani Cooperation, and this reasearch also did some interview to the UMK traders who have been member of both coorporation in the city of Padangsidimpuan. The result of U Test (The Mann-Whitney Test) shown that variable of Capital and Income by the month is more minor Z value acount than Z table, until can be conclude that there is a difference between Bina Bersama Saving-loan Cooperation and BMT Insani cooperation to developed UMK in city of Padangsidimpuan. Meanwhile, the variable of developing business partner, enterprise protection, and people’s satisfication level to cooperation service shown that acount Z is in between Z value table, it is -1,96 < Zh < +1,96 so can be conclude that there is no differencities between Bina Bersama Saving-loan cooperation and BMT Insani Cooperation to developed UMK in city of Padangsidimpuan.Keywords : Capital, Income, Business Partner Developing, Enterprise Protection and People’s Satisfication Level to Cooperation Service.